SOCIOLINGUISTICAL PROBLEMS OF GENERATIONS - Mizababayeva Kamola Uralovna (Western European Studies, 2024)
One of the most significant languages in the world is English. It is spoken by millions of people worldwide and is the language of international business. However, learning English can be among the more challenging languages. English is difficult to master because there are many rules and exceptions to the norms. But millions have shown that it is possible. Participants and external observers alike have a strong propensity to view language change as a process that occurs across immobile generational grids. Nevertheless, age must be viewed as a component of identity that is just as complex and constructed as gender, race, or class—not merely as an independent variable. This holds particularly true in situations where there is a shift in language. In this essay, I critically examine how linguists and linguistic anthropologists have used the concepts of youth identity and intergenerational relations, and I provide some recommendations for future research on the linguistic aspects of generational identity.
Keywords: cultural category; changes in language; generational issue